Project flow optimization from sales to procurement by applying value stream mapping : Case Promeco Group Oy - Lilja, Elias (My University, 2021)
Many industrial companies all over the world are struggling to stay competitive in the market. Due to global competition, businesses are forced to find more productive and adaptable methods to manage increasing customer expectations. Starting the Lean journey is one key to competitiveness, efficiency, and productivity. This research examines project flow optimization from sales to procurement in a defined product group. The project flow under review covers operations from sales, project management, work planning, production planning, engineering, procurement, and production support. This research is conducted as a development project for Promeco Group Oy, an esteemed contract manufacturer of electromechanical systems and services. The objectives of the research are to 1) identify how the project flows in its baseline condition from sales to procurement, 2) Identify the factors that prevent streamlined and Lean flow in the current state, 3) Redesign the flow to meet the requirements of product group X, 4) Define improvements that are required to achieve the future state, 5) Analyze the resources that are needed to implement the findings, 6) Identify shares of VA, NVA and NNVA activities from the flow. To address these objectives, Lean is implemented to the case company by applying value stream mapping that is a Lean tool for identifying waste burdening the process performance. The development project reported in the research is a qualitative case study that validates the findings through data triangulation. Primary data collection methods for the research are current and future state workshops that are held at the company premises. Additionally, multiple meetings and interviews are arranged. Secondary data such as quantitative data from the ERP-system, archived project documentation, project schedule, and project management model are used to deepen the analysis and to verify the primary data findings. In the first workshop, the baseline condition was identified as illogical, over 20 factors straining the smooth and Lean flow were recognized. Many readjustments were made to the future state, and over 25 development ideas optimizing and streamlining the flow were brainstormed. Summary process metrics were calculated for each current and future state results. If all the development ideas that are required to achieve future state are implemented after the project, key figures demonstrating the directive potential between current and future state are: 1) 37,8 % decrease in process steps, 2) 6 % increase in process cycle efficiency, 3) 33,6 % decrease in the total lead time of the flow. Additionally, 44,1 % decrease in process waste will be achieved after the implementation of the future state.

Monet teollisuusyritykset ympäri maailman kamppailevat pysyäkseen kilpailukykyisinä markkinoilla. Globaalin kilpailun vuoksi yritykset joutuvat etsimään tuottavampia ja mukautuvampia menetelmiä hallitakseen kasvavia asiakasodotuksia. Lean-muutoksen aloittaminen on yksi kilpailukyvyn, tehokkuuden ja tuottavuuden avaimista. Tässä tutkielmassa tarkastellaan projektin virtauksen optimointia myynnistä hankintaan määritellyssä tuoteryhmässä. Tutkimuksen keskiössä oleva projektin virtaus kattaa myyntiä, projektinhallintaa, työnsuunnittelua, tuotannonsuunnittelua, konetekniikkaa, hankintaa ja tuotannon tukea koskevat toiminnot. Tämä tutkielma on toteutettu kehitysprojektina yritykselle Promeco Group Oy, joka on arvostettu sähkömekaanisten järjestelmien ja palveluiden sopimusvalmistaja. Tutkielman tavoitteena on 1) tunnistaa, miten projekti etenee perustilassaan myynnistä hankintaan, 2) tunnistaa tekijät, jotka estävät virtaviivaisen etenemisen nykytilassa, 3) uudelleensuunnitella virtaus vastaamaan tuoteryhmä X:n vaatimuksia, 4) määritellä vaadittavat parannukset tahtotilan saavuttamiseksi, 5) analysoida resursseja, joita tarvitaan löydösten toteuttamiseksi, 6) tunnistaa VA, NVA ja NNVA -toimintojen osuudet virtauksesta. Näiden tavoitteiden saavuttamiseksi Lean-ajattelua jalostetaan kohdeyritykseen soveltamalla arvovirtakartoitusta, joka on työkalu prosessin suorituskykyä rasittavan jätteen tunnistamiseen. Tutkielmassa raportoitu kehitysprojekti on laadullinen tapaustutkimus, joka tarkistaa löydökset aineistotriangulaation avulla. Tutkielman ensisijaiset aineistonkeruumenetelmät ovat nykytilan ja tahtotilan työpajat, jotka järjestetään yrityksen toimitiloissa. Lisäksi järjestetään useita kokouksia ja haastatteluita. Toissijaista aineistoa, kuten kvantitatiivista tietoa ERP- järjestelmästä, arkistoitua projektidokumentaatiota, projektiaikataulua ja projektinhallintamallia käytetään analyysin syventämiseksi ja ensisijaisilla ainestonkeruumenetelmillä löydettyjen havaintojen vahvistamiseksi. Ensimmäisessä työpajassa virtauksen perustila tunnistettiin epäloogiseksi, ja yli 20 virtausta rasittavaa tekijää tunnistettiin. Tahtotilaan tehtiin monia uudelleenjärjestelyjä, ja yli 25 kehitysideaa, jotka optimoivat ja virtaviivaistavat projektin etenemistä, ideoitiin. Sekä nyky- että tahtotilan tuotoksille laskettiin prosessin suorituskyvyn mittarit. Jos kaikki tahtotilan saavuttamiseksi vaadittavat kehitysideat toteutetaan kehitysprojektin jälkeen, suuntaa antavaa potentiaalia kuvaavat avainluvut tilojen välillä ovat: 1) 37,8 %:n lasku prosessin vaiheissa, 2) 6 %:n kasvu prosessisyklin tehokkuudessa, 3) 33,6 %:n lasku virtauksen kokonaisläpimenoajassa. Lisäksi 44,1 %:n lasku prosessin jätteen määrässä saavutetaan tahtotilan toteutuessa.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management